1987
DOI: 10.5465/ame.1987.4275731
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Mask: The Politics of Employee Appraisal

Abstract: is really no getting around the fact that whenever I evaluate one of my people, I stop and think about the impact-the ramifications of my decisions on my relationship with the guy and his future here. I'd be stupid not to. Call it being politically minded, or using managerial discretion, or fine tuning the guy's ratings, but in the end I've got to live with him, and I'm not going to rate a guy without thinking about the fallout. There are a lot of games played in the rating process and whether we [managers] ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
295
1
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(308 citation statements)
references
References 1 publication
4
295
1
8
Order By: Relevance
“…He also proposed that if there are norms that make raters become more lenient, then they will tend to rate the performance appraisal with high marks. Similarly, Longenecker, Sims and Gioia (1987) found that raters tend to appraise inaccurately when top management not taking performance appraisal process seriously. Raters having such feelings tend not to be committed to appraise accurately since the top management is not commited either.…”
Section: B Raters' Perceived Subjective Norms Towards Appraising Accmentioning
confidence: 98%
See 2 more Smart Citations
“…He also proposed that if there are norms that make raters become more lenient, then they will tend to rate the performance appraisal with high marks. Similarly, Longenecker, Sims and Gioia (1987) found that raters tend to appraise inaccurately when top management not taking performance appraisal process seriously. Raters having such feelings tend not to be committed to appraise accurately since the top management is not commited either.…”
Section: B Raters' Perceived Subjective Norms Towards Appraising Accmentioning
confidence: 98%
“…Decotiis and Petit (1978) argued that the perceived consequences of accurate appraisal partly determine raters' motivation to appraise accurately. Longenecker, Sims, and Gioia (1987) found that raters tried to manipu-late the performance appraisal when they failed to see goodness in giving accurate appraisal. When the consequences of accurate appraisal is negative, raters tend to have negative attitudes towards appraising accurately; hence their intention to appraise accurately will be low and vice-versa.…”
Section: A Raters' Attitude Towards Appraising Accuratelymentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth-interviews with 60 upper-level executives undertaken by Longenecker et al (1987) showed that the managers' own aims and interests influenced the appraisals: 'Managers made it clear that they would not allow excessively accurate ratings to cause problems for themselves, and that they attempted to use the appraisal process to their own advantage ' (ibid. : 191).…”
Section: Subjective Performance Appraisalssome Sources Of Errormentioning
confidence: 99%
“…Indeed, it has been claimed that the organizational and political context of performance appraisal can exert a stronger influence on performance ratings than appraiser capabilities and limitations (Murphy & Cleveland, 1995). As a result, researchers have been interested in identifying how political processes can influence HR procedures such as executive appraisal and selection (Bozionelos, 2005;Fletcher, 2001;Gioia & Longenecker, 1994;Longenecker, Sims & Gioia, 1987). The following section looks at two ways in which power and politics are important for HR processes and I/O psychology.…”
Section: A Political View Of Human Resource Managementmentioning
confidence: 99%